Strategi Gerakan Minoritas Arab-Israel dalam Memperjuangkan Kesetaraan Hak di Tengah Diskriminasi Sistemik - Muhammad Abdillah Ihsan (Milenial: Journal for Teachers and Learning, 2025)
This research analyzes the strategy of the Arab-Israeli minority movement in fighting for equal rights amidst systemic discrimination institutionalized through state policies such as the Nation-State Law. Using a qualitative approach and case studies, research reveals that Arab-Israeli society developed various forms of resistance that are fragmented but remain committed to Israel's legal framework, including constitutional struggles through the courts, grassroots movements such as the Islamic Movement that provide alternative social services, as well as political participation through Arab parties in the Knesset such as the United Arab List, Hadash, and Balad. The research findings show that despite Israel's high commitment to democracy, fragmentation within political and social movements—caused by ideological and interest differences—is a significant obstacle in creating effective pressure to achieve full equality. This research concludes that the consolidation of the movement through an inclusive coordination platform and the building of strategic alliances with progressive Jewish groups is a crucial step to optimize the political struggle of the Arab-Israeli minority towards recognition as equal citizens.